2012
DOI: 10.7314/apjcp.2012.13.6.2721
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Endoscopy and Upper Gastrointestinal X-ray for Gastric Cancer Screening in South Korea: A Cost-utility Analysis

Abstract: Background: There are limited data evaluating the cost-effectiveness of gastric cancer screening using endoscopy or upper gastrointestinal x-ray in the general population. Objective: To evaluate the costeffectiveness of population-based screening for gastric cancer in South Korea by decision analysis. Methods: A time-dependent Markov model for gastric cancer was constructed for healthy adults 30 years of age and older, and a deterministic sensitivity analysis was performed. Cost-utility analysis with multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 26 publications
1
45
0
4
Order By: Relevance
“…This finding is consistent with previous research showing improved efficacy and usefulness of endoscopy compared to UGI X-ray screening (Kim et al, 2000;Tsubono and Hisamichi, 2000). Because the cost of endoscopy examination of Korea is considerably lower than the UGI examination cost, the incremental costs of endoscopy screening were competitive in Korea (Chang et al, 2012). A previous report found that until the cost of endoscopy screening was 3-fold more than a UGI series, the endoscopy method should be the dominant strategy over UGI in Korea (Lee et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This finding is consistent with previous research showing improved efficacy and usefulness of endoscopy compared to UGI X-ray screening (Kim et al, 2000;Tsubono and Hisamichi, 2000). Because the cost of endoscopy examination of Korea is considerably lower than the UGI examination cost, the incremental costs of endoscopy screening were competitive in Korea (Chang et al, 2012). A previous report found that until the cost of endoscopy screening was 3-fold more than a UGI series, the endoscopy method should be the dominant strategy over UGI in Korea (Lee et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…First, the study subjects were not a cohort group but the entire population of Korea, subjects who underwent NCSP gastric cancer screening in baseline. Although there have been a couple of reports investigating the cost-utility outcomes of gastric cancer screening, those Markov models were constructed based on a hypothetical cohort group (Gupta et al, 2011;Chang et al, 2012). Using large and absolute data from the whole population, this research could produce unconditional performance outputs of NCSP with no selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prognosis is generally favorable in early gastric cancers after radical surgery, with a 5-year survival rate of more than 90% (Hyung et al, 2002;Kwee et al, 2008). The proportion of early gastric cancer among all gastric cancers has increased to nearly 50% in Japan and Korea (Chang et al, 2012;Tatematsu et al, 2013). With more widespread mass screenings, as well as advances in endoscopic techniques and equipment, similar trends have been observed during the past few decades in China.…”
Section: Introductionmentioning
confidence: 99%